Hubungan Pemberian Asi Ekslusif, Pengetahuan Ibu dan Dukungan Keluarga Terhadap Kejadian Stunting di Desa Panton Kecamatan Nisam Aceh Utara - Dian Rahayu; Gelva Irayana; Ambia Nurdin; Khairuman Khairuman (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Stunting is a health problem that is still a concern in Indonesia, including in Panton Village, Nisam District, North Aceh. This village has a fairly high stunting rate, influenced by various factors such as exclusive breastfeeding, maternal knowledge, and family support. This study aims to analyze the relationship between exclusive breastfeeding, maternal knowledge, and family support on the incidence of stunting in Panton Village. The study used an observational analytical design with a cross-sectional approach and involved 30 respondents selected by purposive sampling. Data were collected through questionnaires and analyzed using the chi-square test with a significance level of 0.05. The results showed that there was a significant relationship between exclusive breastfeeding and the incidence of stunting (p = 0.003). In addition, maternal knowledge was also related to the incidence of stunting (p = 0.005). Family support also had a significant relationship to the incidence of stunting (p = 0.001). In conclusion, exclusive breastfeeding, maternal knowledge, and family support play an important role in preventing stunting. Therefore, it is suggested to health workers, especially the health promotion and nutrition division, to improve education for mothers and families regarding the importance of exclusive breastfeeding, balanced nutrition, and parenting patterns that support optimal child growth.